2014
DOI: 10.1007/s00442-014-3143-z
|View full text |Cite
|
Sign up to set email alerts
|

Competitive interactions between established grasses and woody plant seedlings under elevated CO2 levels are mediated by soil water availability

Abstract: The expansion of woody plants into grasslands has been observed worldwide and is likely to have widespread ecological consequences. One proposal is that woody plant expansion into grasslands is driven in part by the rise in atmospheric CO2 concentrations. We have examined the effect of CO2 concentration on the competitive interactions between established C4 grasses and woody plant seedlings in a model grassland system. Woody plant seedlings were grown in mesocosms together with established C4 grasses in three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 50 publications
2
36
0
Order By: Relevance
“…There is a large body of experimental work that has provided us with a wealth of understanding on the responses of temperate grasslands to changes in precipitation patterns, including extreme drought (Cherwin & Knapp, ; Fay, Carlisle, Knapp, Blair, & Collins, ; Heisler‐White, Blair, Kelly, Harmoney, & Knapp, ; Heisler‐White, Knapp, & Kelly, ; Knapp et al, ; Thomey et al, and others). However, rainfall manipulation studies in savannas are currently very limited (but see February et al, , Manea & Leishman, ). Experimental manipulations in the field can be logistically challenging, particularly in the presence of fire and mega‐herbivores such as elephants, but are needed to better understand how changes in the intensity, duration and timing of droughts influence vegetation responses across diverse savanna types.…”
Section: The Way Aheadmentioning
confidence: 99%
“…There is a large body of experimental work that has provided us with a wealth of understanding on the responses of temperate grasslands to changes in precipitation patterns, including extreme drought (Cherwin & Knapp, ; Fay, Carlisle, Knapp, Blair, & Collins, ; Heisler‐White, Blair, Kelly, Harmoney, & Knapp, ; Heisler‐White, Knapp, & Kelly, ; Knapp et al, ; Thomey et al, and others). However, rainfall manipulation studies in savannas are currently very limited (but see February et al, , Manea & Leishman, ). Experimental manipulations in the field can be logistically challenging, particularly in the presence of fire and mega‐herbivores such as elephants, but are needed to better understand how changes in the intensity, duration and timing of droughts influence vegetation responses across diverse savanna types.…”
Section: The Way Aheadmentioning
confidence: 99%
“…Work by Ward and Esler (2010) showed that encroachment by Acacia species is suppressed by water competition from grasses. Furthermore, recent work by Manea and Leishman (2015) showed that, under elevated CO 2 conditions, the growth of C 4 grasses increases greatly, resulting in greater leaf area. This in turn, restricts light and water to tree seedlings, suppressing their growth and offsetting the benefits provided by increased moisture availability resulting from reduced stomatal conductance.…”
Section: Global Driversmentioning
confidence: 99%
“…Although we found that elevated CO 2 levels do not directly favours a particular sprouting type, it may affect their interactions with other co-occurring plant species. For example, woody plant seedling establishment in grasslands in the future will be strongly coupled to the CO 2 response and subsequent competitive effect of the grass species within those systems (Manea and Leishman 2015). Several studies have shown that elevated CO 2 levels stimulate biomass production in grasslands when resources are not limited (Morgan et al 2001;Shaw et al 2002;Dijkstra et al 2010) which may reduce woody plant seedling establishment success (Manea and Leishman 2015).…”
Section: Discussionmentioning
confidence: 99%